ywilfred wrote:

x^2-y^2 = (x + 5)(y - 5)

x^2 - y^2 = xy -5x + 5y - 25

x^2 = y^2 + 5 (y - 5 - x)

x^2 = y^2 only when y-x = 5 which we do not know if this is so.

Ans B

Statement 2 is sufficient but I relly could not evalute statement 1!

ywilfred

x^2 - y^2 = xy -5x + 5y - 25

x^2 = y^2 + 5 (y - 5 - x)

+xy
so analysis fails there!

Statement 1 si true for x=y=+5 or x=y=-5

But I can not say for sure that these are the only values which satisfy this equation!

And I can not come up with any values which justify this equation except above one!

Anyone has mathemitical proof why statement 1 will be sufficient or not!

What is OA/OE